Brown Tumors Secondary to Tertiary Hyperparathyroidism Masquerading as Lytic or Sclerotic Skeletal Metastases on Preoperative/Postoperative 18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography: A Case Report - ENGÜR, CEREN ÖZGE; ÖNEŞ, TUNÇ; FİLİZOĞLU, NUH; KESİM, SELİN; ÖZGÜVEN, SALİH (My University, 2022)
Tertiary hyperparathyroidism (TH) is a rare condition that develops from secondary hyperparathyroidism in cases when the secretion becomes autonomous. Brown tumors (BTs) are rare skeletal lesions of hyperparathyroidism that may mimic cancer metastasis. We report a case of a patient who was diagnosed with TH with multiple BTs which mimics osteolytic/osteoblastic metastases that were evaluated with two fluorodeoxyglucose positron emission tomography scans with an interval of 23 months in the preoperative and postoperative period.
Keywords: Tıp; Dahili Tıp Bilimleri; Nükleer Tıp; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Nuclear medicine; Health Sciences; RADYOLOJİ, NÜKLEER TIP ve MEDİKAL GÖRÜNTÜLEME; Klinik Tıp; Klinik Tıp (MED); RADIOLOGY, NUCLEAR MEDICINE & MEDICAL IMAGING; CLINICAL MEDICINE; Clinical Medicine (MED); Radyoloji ve Ultrason Teknolojisi; Radyoloji, Nükleer Tıp ve Görüntüleme; Radiological and Ultrasound Technology; Radiology, Nuclear Medicine and Imaging; Brown tumors; fluorodeoxyglucose positron emission tomography/computed tomography; osteoblastic metastases; osteolytic metastases; tertiary hyperparathyroidism; GIANT-CELL TUMOR; FDG-PET; F-18-FDG PET/CT; BENIGN; CT; Brown tumors; fluorodeoxyglucose positron emission tomography/computed tomography; osteoblastic metastases; osteolytic metastases; tertiary hyperparathyroidism